2010
DOI: 10.1007/s10853-010-5113-0
|View full text |Cite
|
Sign up to set email alerts
|

Review of the anatase to rutile phase transformation

Abstract: Titanium dioxide, TiO 2 , is an important photocatalytic material that exists as two main polymorphs, anatase and rutile. The presence of either or both of these phases impacts on the photocatalytic performance of the material. The present work reviews the anatase to rutile phase transformation. The synthesis and properties of anatase and rutile are examined, followed by a discussion of the thermodynamics of the phase transformation and the factors affecting its observation. A comprehensive analysis of the rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

128
1,767
9
93

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 2,835 publications
(1,997 citation statements)
references
References 191 publications
(295 reference statements)
128
1,767
9
93
Order By: Relevance
“…The tetragonal rutile phase was formed during the annealing of TiO 2 samples in temperatures between 600 and 800 °C, however, the complete formation of rutile phase just was observed at sample using high temperature above 800°C. These observations corroborate with literature for titania powder, rutile transformation takes place at around 780 °C, material derived of sol-gel process 17 .…”
Section: Resultssupporting
confidence: 92%
“…The tetragonal rutile phase was formed during the annealing of TiO 2 samples in temperatures between 600 and 800 °C, however, the complete formation of rutile phase just was observed at sample using high temperature above 800°C. These observations corroborate with literature for titania powder, rutile transformation takes place at around 780 °C, material derived of sol-gel process 17 .…”
Section: Resultssupporting
confidence: 92%
“…TiO 2 occurs in different crystalline phases which are rutile, anatase and brookite 21,22,23 . The current study follows on the work of Shimura et al 24 in which they showed the effect of the TiO 2 crystal phase on the activity of TiO 2 -supported cobalt catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The PC activity can also be improved by mixing the two phases (80% anatase and 20% rutile) due to charge carrier separation attained as a result of confinement of photoexcited carriers in the different phases which leads to reduced recombination. The surface roughness has been reported to have a negligible effect on the PC activity of single crystalline rutile TiO 2 [17]. According to Hernandez-Alonso et al [18] an increase in the surface area of the photocatalyst is accompanied by an increase in the probability of formation of lattice defects.…”
Section: Tio 2 Antifouling and Photocatalytic Activitymentioning
confidence: 99%